Development of an automated smart room controller using ATMEL AT89S52 - Emi Izhanizam, Azmi (Universiti Sains Malaysia (USM), 2014)
When electrical appliances are used without any surveillance, the cost of electricity increases. The cost may increase further when there are air-conditioners involved. It has been foreseen that in the year 2020, all electrical appliances will be controlled automatically. A system which can accommodate such functionalities is a smart system. One type of smart system is a smart room system. It is an information technology, computer-based system which facilitates human in controlling the use of appliances and hence, reduce the cost of electricity. Although there have been various smart home systems nowadays, not all has incorporated a built-in display panel to facilitate the control of the electrical-appliances and rooms. Therefore, this project focuses on designing and developing a smart room with a display panel using a microcontroller. The smart room system has three main objectives. The first objective is to develop the main software to automatically control all the electrical appliances in the smart room. The second objective is to build a display panel for controlling the number of occupants and the electrical appliance in the room. The last objective involves the development of a system that automatically controls the use of the air-conditioners and fans, depending on the room temperature. The main works of this project include the development of a smart sensor system, home automation system, the main software and the integrated model. The final phase of the project involves developing the smart room prototype. The successfully developed microcontroller components have been tested and found to be fully functioning. Such a system has shown to be useful in that it provides users with an efficient environment as all appliances can be automatically controlled by a computer. Moreover the users can in real-time, observe up-to-date information of their smart room condition through a built-in display panel.